Solidaritas Sosial, Media, dan Pengorganisasian Aksi Kolektif (Studi Kasus Komunitas Nelayan Pulau Lae-Lae dalam Konteks Reklamasi) - Idrus, Idham Irwansyah; Mappe, Ulfa Utami; Sunaniah, Sunaniah (The Journal of Society and Media, 2025)
This study aims to identify the mechanisms of social‑media use, primarily Instagram and WhatsApp groups, in building social awareness on Lae‑Lae Island, and to analyse the role of social media in organising collective actions of the Lae‑Lae Island fishermen community. The reclamation plan triggers resistance because it is perceived to threaten both the marine ecosystem and the livelihoods of residents. This research employs a qualitative approach, utilising a case-study method, which involves in-depth interviews with eight key informants purposively selected, participant observation in both physical and digital spaces, and document analysis of content and visuals. The study is analysed using resource-mobilisation theory and relational network‑solidarity theory. Findings show that the media play an important role in facilitating the formation of social solidarity among the fishing community. Social media shape collective identity, become a space for sharing information and joint narratives that strengthen the consensus against reclamation, and also serve as a digital mobilisation tool for organising collective actions. The synergy between solidarity networks, activists, NGOs, students, the Kawal Pesisir alliance, and community members supported by media communication strategies strengthens the fishermen community’s capacity to mobilise resources, formulate demands, influence public opinion, and sustain the anti‑reclamation movement on Lae‑Lae Island.